Rural Electricity Distribution Systems in Ghana: Analysis and Verification of Selected Design Factors (Journal of Science and Technology, 2016)
Rural electrification is a strategic component of economic development in Ghana. Its execution has led to rapid growth in sub-transmission line extensions and installation of new transformers, with problems that require analysis. Issues related to the sizing of transformers and line extensions are dealt with here. In particular the degree of penetration of appliances and energy consumption have been used to forecast loads for sizing of transformers. Other issues such as high voltage drops and voltage imbalance have been considered. Data obtained from measurements in three towns were used to verify load factors normally assumed in distribution network design. The parameters of the 33-kV line serving Bekwai from Kumasi were used to analyse voltage regulation, and to determine additional line extensibility and loadability based on the MVA.km as a transmission factor.